Cu and Zn contents in soil profiles of different lithologies in Santa Catarina Teores de Cu e Zn em perfis de solos de diferentes litologias em Santa Catarina - Hugen C.* (2013)
Heavy metals occur in the soil through the weathering of rocks rich in these elements. The objective of this study was to evaluate the contents of Cu and Zn in 58 modal profiles of the major soil types of the State of Santa Catarina, collected in natural soils without anthropogenic interference, and derived from different lithologies. One hundred and eleven soil samples were used from the A and B horizons. The Cu and Zn elements were extracted with Aqua Regia method and quantified by atomic absorption. For the analysis of the results, the data was categorized using as variables the concentrations of Cu and Zn, and the effect of genetic horizon, profile, and rock material on the distribution of these metals using univariate techniques was evaluated. The sampled soils for this study are mostly derived from igneous rocks, which reflects the significant amount of soil derived from these materials in the state. The results indicate that the concentrations of Cu and Zn in South Brazilian soils are related to the geochemical composition of the rock material. So, these elements can be used to indicate the influence of different lithologies and the baseline concentration to environmental monitoring.